Students’ Islamic Senior High School 3 Kampar Interest in Learning Arabic : Students’ Islamic Senior High School 3 Kampar Interest in Learning Arabic - Wardatul Wahidah; Saproni; Rojja Pebrian ((الطموحات ) EL-THUMUHAT, 2021)
The purpose in this research examined to know students’ class XI interest level in learning Arabic at Islamic Senior High School 3 Kampar. This research used quantitative research. The population took all students at Islamic Senior High School 3 Kampar in 384 students. The sample took all class XI students in 88 students. Sampling technique used purposive sampling, where it was taken based on characteristic or population attitude that was known before, and the criterion as follows: inclusion criteria: active students at Islamic Senior High School 3 Kampar, all class XI students. Exclusion criteria: all class X students, all class XII students. Data collection technique used observation, questionnaire and documentation as supporting data. Observation was used to do observation to students. Questionnaire was used to know students’ interest level in learning Arabic. Research finding showed that students’ Islamic Senior High School 3 Kampar Learning Interest in learning Arabic was 68.43% and it meant that was in middle category.